PENERAPAN METODE PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA - SRI HARTONO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The science learning outcomes of SMP Negeri 2 Jatisrono students are low because the learning methods applied by teachers are still less varied. In order to overcome these problems, a more varied learning method is needed, namely by applying the Student Teams Achievement Division (STAD) cooperative learning method. The purpose of this study is to improve the science learning outcomes of class VIII C students of SMP Negeri 2 Jatisrono in the 2015/2016 academic year through the application of the STAD learning method. This research is a Classroom Action Research (CAR) which is taken in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. Each cycle consists of two meetings. The subjects of the research were students of class VIII C of SMP Negeri 2 Jatisrono, totaling 28 students. The instrument used to measure student learning outcomes is a written test in the form of multiple choice. The instrument to determine student learning motivation is in the form of an observation sheet to determine the increase in student learning motivation in the implementation of the STAD learning method. The results showed that the STAD learning method could improve student learning outcomes. In the first cycle, 9 students did not reach the KKM and 19 students reached the KKM. In the second cycle as many as 5 students did not reach the KKM and 23 students reached the KKM. The learning mastery of class VIII C students in the initial condition was 46%, increased in the first cycle to 68%. Mastery of student learning increased to 82% in the second cycle. The class average score increased by 8 points from 74 in the first cycle to 82 in the second cycle. STAD learning method plays a role in increasing students' learning motivation. This is indicated by an increase in the number of scores in the first cycle, the percentage of students' learning motivation is 62.1%. In the second cycle, the percentage of learning motivation was 81,1%. When compared, students' learning motivation from cycle I to cycle II increased by 19,0%. ABSTRAKHasil belajar IPA siswa SMP Negeri 2 Jatisrono tergolong rendah karena metode pembelajaran yang diterapkan oleh guru masih kurang variatif. Guna mengatasi permasalahan tersebut diperlukan suatu metode pembelajaran yang lebih variatif , yaitu dengan menerapkan metode pembelajaran kooperatif Student Teams Achievement Division (STAD). Tujuan penelitian ini adalah peningkatan hasil belajar IPA siswa kelas VIII C SMP Negeri 2 Jatisrono tahun pelajaran 2015/2016 melalui penerapan metode pembelajaran STAD. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang ditempuh dalam dua siklus. Setiap siklus terdiri dari empat tahap yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Setiap siklus terdiri dari dua kali pertemuan. Adapun yang menjadi subjek penelitian adalah siswa kelas VIII C SMP Negeri 2 Jatisrono yang berjumlah 28 siswa. Instrumen yang digunakan untuk mengukur hasil belajar siswa berupa tes tertulis dalam bentuk pilihan ganda. Instrumen untuk mengetahui motivasi belajar siswa berupa lembar observasi untuk mengetahui peningkatan motivasi belajar siswa dalam pelaksanaan metode pembelajaran STAD. Hasil penelitian menunjukkan bahwa metode pembelajaran STAD dapat meningkatkan hasil belajar siswa. Pada siklus I sebanyak 9 siswa yang tidak mencapai KKM dan 19 siswa mencapai KKM. Pada siklus II sebanyak 5 siswa tidak mencapai KKM dan 23 siswa mencapai KKM. Ketuntasan belajar siswa kelas VIII C pada kondisi awal 46%, mengalami peningkatan pada siklus I menjadi 68%. Ketuntasan belajar siswa semakin meningkat menjadi 82% pada siklus II. Nilai rata-rata kelas meningkat sebesar 8 poin dari 74 pada siklus I, menjadi 82 pada siklus II. Metode pembelajaran STAD berperan dalam meningkatkan motivasi belajar siswa. Hal ini ditunjukkan peningkatan jumlah skor pada siklus I persentase motivasi belajar siswa sebesar 62,1%. Pada siklus II dihasilkan persentase motivasi belajar sebesar 81,1%. Apabila dibandingkan, motivasi belajar siswa dari siklus I ke siklus II mengalami kenaikan sebesar 19,0%.